Cement Viscosity and Application Time Lead to Significant Changes in Cement Penetration and Contact Surface Area - Christian Fölsch, Prof Dr med; Julia Schirmer; Cosmin Glameanu; Bernd Ishaque, Prof Dr med; Carlos Alfonso Fonseca Ulloa, Dr biol hom; Torben Harz; Markus Rickert, Prof Dr med; John Ryan Martin, MD; Jan Scherberich, Dr rer nat; Jessica Steinbart; Gabriele Krombach, Prof Dr med; Christian Paul; et al. (Arthroplasty Today)
Background: Application time and viscosity are factors that can significantly affect the properties of bone cement and implant fixation. The aim of this study was to investigate the influence of different application times of 2 different cements on mechanical parameters, cement interdigitation, and cement distribution. Methods: P.F.C. Sigma tibial trays were cemented with high-viscous Palacos R and medium- to low-viscous Simplex P in an open-cell model. The application was performed at different times within the manufacturer’s specifications. Cement interdigitation and micromotion were measured with computed tomography scan using a novel method. Results: Significant differences of insertion forces were found at all times of cement application. Cement penetration decreased with increasing pressure and viscosity. No significant differences were shown for micromotion between Palacos R and Simplex P except for an increase for Simplex P from 3 to 7 minutes at the bone-cement interface. Simplex P appeared to trap air at the implant-cement interface at 3 minutes and increased at 7 minutes. Conclusions: Cement distribution and intrusion of Palacos R and Simplex P decreased with time. Simplex P trapped air at the implant-cement interface, decreasing the amount of contact at the implant-cement interface, which is worrisome for long-term implant fixation. Given the significant changes in cement properties after mixing, it is necessary for surgeons to understand the viscosity and timing of cement application to achieve optimal cement penetration and surface contact area to potentially decrease implant loosening. High-viscous Palacos R should be applicated immediately with doughing time and medium-viscous Simplex P for about 4 minutes considering a threshold of minimum pressure.